2020
DOI: 10.46586/tosc.v2020.i1.233-265
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis of Forkciphers

Abstract: The forkcipher framework was designed in 2018 by Andreeva et al. for authenticated encryption of short messages. Two dedicated ciphers were proposed in this framework: ForkAES based on the AES (and its tweakable variant Kiasu-BC), and ForkSkinny based on Skinny. The main motivation is that the forked ciphers should keep the same security as the underlying ciphers, but offer better performances thanks to the larger output. Recent cryptanalysis results at ACNS ’19 have shown that ForkAES actually offers a reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“….,ST K 20 , ST K 48 , ST K 49 , ..., ST K 74 . As pointed out in [BDL20], there are some master key differences δs that satisfy δ = LF SR2 15 (δ). So we can get differential characteristics with 6 consecutive inactive subtweakeys ST K 18 , ST K 19 , ST K 20 , ST K 48 , ST K 49 and ST K 50 .…”
Section: Active Cellmentioning
confidence: 99%
See 1 more Smart Citation
“….,ST K 20 , ST K 48 , ST K 49 , ..., ST K 74 . As pointed out in [BDL20], there are some master key differences δs that satisfy δ = LF SR2 15 (δ). So we can get differential characteristics with 6 consecutive inactive subtweakeys ST K 18 , ST K 19 , ST K 20 , ST K 48 , ST K 49 and ST K 50 .…”
Section: Active Cellmentioning
confidence: 99%
“…Lemma 1. [BDL20] For any given SKINNY S-box S and any two non-zero differences δ in and δ out , the equation S i (y) ⊕ S i (y ⊕ δ in ) = δ out has one solution on average. [DKS10], the N dround cipher E is considered asẼ 1 • E m •Ẽ 0 , whereẼ 0 , E m ,Ẽ 1 contain r 0 , r m , r 1 rounds, respectively.…”
Section: The Tradeoff In Rectangle Attack On Ciphers With Linear Key-schedulementioning
confidence: 99%
“…The variants of the ForkAE family are listed below. [117] showed that attacks on Skinny can be extended to one extra round for most ForkSkinny variants and up to three rounds for ForkSkinny-128-256. Privacy and authenticity proofs of PAEF and SAEF in the nonce-respecting scenario were provided in [40].…”
Section: Forkaementioning
confidence: 99%
“…Banik et al [5] introduced reflection differential trails and proposed some attacks of ForkAES- * -4-4 ( * is any nonnegative integer). Bariant et al [6] first presented truncated differential attacks on ForkAES- * -5-5 (full ten rounds) in reconstruction queries, but the security of ForkAES in encryption queries needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with paper [5], we carefully consider the process of recovering the master key, which can reject wrong candidate keys efficiently. Compared with paper [6], we consider the attack scenario in encryption queries, which increases the understanding of ForkAES. To the best of our knowledge, we improve the previous attacks on ForkAES by attacking one more round in encryption queries.…”
Section: Introductionmentioning
confidence: 99%